3D printing for bare foot running shoes - Yusman, Mohamed Hanis (2017)
Barefoot running is the act of running without the use of shoes or with minimal feet protection. There are substantial debates on barefoot running and its effectiveness in preventing running injury as compared to the conventional shod running. One problem with barefoot running is that it can cause musculoskeletal injuries to habitually shod runners, especially to the metatarsals, calf muscles and Achilles tendon. This is due to the change in gait and difference in muscle usage when transitioning from shod to barefoot running. On the other hand, numerous studies and research have found some common habitual characteristic in runners who engage in barefoot running. They include the betterment of the proprioceptive feedback, the shortening of running strides hence increasing the stride frequency, avoidance of the Rear Foot Strike (RFS) and employment of the Forefoot Strike (FFS), avoidance of impact peaks when running on hard surface and maintaining of low joint moments. These theories help in further understanding the advantages of barefoot running over conventional shod running, but not exclusively on injury prevention. A previous study by Li (2016), concentrated on the investigation of stress distribution and concentration of forefoot strike (FFS) running pattern and on a coupled FE model of a foot and barefoot running footwear. Through the study, this project could identify the areas of the foot that requires attention to minimize the risks of barefoot running injury, and with the help of advanced 3D printing technology, develop a concept for a biomechanically refined barefoot running shoe. Proof of concept is developed through the review of various literatures, presentation of design ideas and finally a fabrication of a product prototype. The literature reviews covered in this project are the biomechanics of the foot and barefoot running, foot orthotics and support, exploration of 3D CAD modelling and 3D prototyping and market researches of current 3D printing for shoes. A prototype was developed and its functions and future work recommendations are being discussed for further improvements in its biomechanical design.